2016
DOI: 10.1097/aln.0000000000001353
|View full text |Cite
|
Sign up to set email alerts
|

Median Effective Dose of Intranasal Dexmedetomidine for Rescue Sedation in Pediatric Patients Undergoing Magnetic Resonance Imaging

Abstract: Background The median effective dose (ED50) of intranasal dexmedetomidine after failed chloral hydrate sedation has not been described for children. This study aims to determine the ED50 of intranasal dexmedetomidine for rescue sedation in children aged 1 to 36 months, who were inadequately sedated by chloral hydrate administration during magnetic resonance imaging (MRI). Methods This study was performed on 120 children, who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…The result match those observed in earlier study. Zhang used intranasal dexmedetomidine as a rescue sedative, the study revealed that ED 50 of intranasal dexmedetomidine was 0.4 μg kg −1 in the age group of 1‐6 months and 1 μg kg −1 in those 25‐36 months, almost doubled in older children . There are several possible explanations for this result.…”
Section: Discussionmentioning
confidence: 99%
“…The result match those observed in earlier study. Zhang used intranasal dexmedetomidine as a rescue sedative, the study revealed that ED 50 of intranasal dexmedetomidine was 0.4 μg kg −1 in the age group of 1‐6 months and 1 μg kg −1 in those 25‐36 months, almost doubled in older children . There are several possible explanations for this result.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine can also be used as a rescue sedative. After failed chloral hydrate sedation, the rescue success rate of dexmedetomidine increases in a dose-dependent manner [27], and the effective dose 50 of dexmedetomidine for rescue increases with age in those younger than 3 years [28]. Compared with chloral hydrate, intranasal dexmedetomidine has a higher rescue success rate than a second dose of chloral hydrate after failed chloral hydrate sedation [29].…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine can also be used as a rescue sedative. After failed chloral hydrate sedation, the rescue success rate of dexmedetomidine increases in a dose-dependent manner 11 , and the effective dose 50 of dexmedetomidine for rescue increases with age in those younger than 3 years 26 . Compared with chloral hydrate, intranasal dexmedetomidine has a higher rescue success rate than a second dose of chloral hydrate after failed chloral hydrate sedation 27 .…”
Section: Choice Of Sedativesmentioning
confidence: 99%